Pengembangan E-Modul Fisika Berbasis AR Terintegrasi Mitigasi Bencana Tanah Longsor untuk Penguasaan Konsep dan Kesiapsiagaan - Maulana, Yudi; Mayub, Afrizal; Johan, Henny (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aims to develop an Augmented Reality (AR)-based physics e-module that integrates landslide disaster mitigation within the topic of work and energy to improve students’ conceptual mastery and disaster preparedness. To support contextual learning, the study also identifies the predominant frequency (f₀), amplification factor (A0), and seismic vulnerability index (Kg) at MAN Insan Cendekia Bengkulu Tengah using the microtremor method. The development followed the 4D model Define, Design, Develop, and Disseminate including needs analysis, product design, expert validation, and both limited and large-scale trials. Expert validation showed the module was highly feasible, with scores of 99% for content and 97% for media. The large-scale trial involved 45 students, namely 30 in the experimental group using the AR-based e-module and 15 in the control group using printed textbooks. Results indicated that the experimental group achieved an average N-Gain of 0.470 (moderate), with 70% of students in the moderate to high category. In contrast, the control group obtained an N-Gain of only 0.180 (low). An independent t-test showed a statistically significant improvement within the experimental group (p = 0.001) and a significant difference between groups (p = 0.000). The Chi-Square test revealed significant differences in cognitive (p = 0.000) and conative (p = 0.003) aspects, while the affective aspect remained statistically insignificant. Overall, the AR-based e-module proves to be a relevant and effective tool to strengthen students’ conceptual understanding and readiness in responding to disaster risks through contextual physics education